2013
DOI: 10.1371/journal.pone.0076664
|View full text |Cite
|
Sign up to set email alerts
|

The Duration of Chlamydia muridarum Genital Tract Infection and Associated Chronic Pathological Changes Are Reduced in IL-17 Knockout Mice but Protection Is Not Increased Further by Immunization

Abstract: IL-17 is believed to be important for protection against extracellular pathogens, where clearance is dependent on neutrophil recruitment and local activation of epithelial cell defences. However, the role of IL-17 in protection against intracellular pathogens such as Chlamydia is less clear. We have compared (i) the course of natural genital tract C. muridarum infection, (ii) the development of oviduct pathology and (iii) the development of vaccine-induced immunity against infection in wild type (WT) BALB/c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
89
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 72 publications
(88 reference statements)
10
89
1
Order By: Relevance
“…The reduced hydrosalpinx was further correlated with a significant reduction in IL-17 production by splenocytes from TNFR1 Ϫ/Ϫ mice. This finding is supported by a recent observation that mice deficient in IL-17 developed significantly reduced chronic pathology (45) and also is consistent with our previous study showing that although the IL-23/TH17 axis was not required for host resistance to C. muridarum infection, it contributed significantly to Chlamydia-induced pathology (20). These observations together have suggested that IL-17-mediated responses are critical for hydrosalpinx development during C. muridarum infection.…”
Section: Figsupporting
confidence: 91%
“…The reduced hydrosalpinx was further correlated with a significant reduction in IL-17 production by splenocytes from TNFR1 Ϫ/Ϫ mice. This finding is supported by a recent observation that mice deficient in IL-17 developed significantly reduced chronic pathology (45) and also is consistent with our previous study showing that although the IL-23/TH17 axis was not required for host resistance to C. muridarum infection, it contributed significantly to Chlamydia-induced pathology (20). These observations together have suggested that IL-17-mediated responses are critical for hydrosalpinx development during C. muridarum infection.…”
Section: Figsupporting
confidence: 91%
“…[8] However,Lu et al have shown that defense from genital infection by means of live Chlamydia immunization correlates with Т-cell response and is characterized by IFNγ high level and IL-17 low level. [9] Andrew et al in their investigation have illustrated that, in IL-17 absence, clinical gravity in chlamydial genital lesions is considerably lessened; [10] like this, in our study, IL-17 level in the chlamydial infection group was not different from the control values.…”
Section: Discussionsupporting
confidence: 84%
“…The same study also revealed that tumor necrosis factor receptor 1 (TNFR1) was critical for hydrosalpinx development following C. muridarum infection, which is consistent with an earlier observation showing an important role of tumor necrosis factor alpha (TNF-␣) in chlamydial induction of hydrosalpinx (14). Many other host molecules have also been shown to contribute to chlamydial pathogenicity in the upper genital tract, including matrix metalloproteinases (15), inducible nitric oxide synthase (16), interleukin 1 (IL-1) receptor (17), caspase 1 (18,19), IL-17 (20), CD28 (21), and CXCR2 (22). However, none of these previous studies have sufficiently addressed whether the reduced pathology was due to reduced oviduct infection, reduced inflammatory responses in the oviduct, or both.…”
supporting
confidence: 90%